E-COMMERCE DALAM PERSPEKTIF FIKIH EKONOMI - Iska, Syukri (JURIS (Jurnal Ilmiah Syariah), 2010)
Economic transactions through electronic commerce (e-commerce) contribute to the vast use of information technology as well as internet nowadays. Its phenomenal development makes Islamic law take part in responding from the perspectives of economic jurisprudence (fiqh). Basically, Islam accommodates any transactions carried out by human as long as there is no single rule that prohibits such transaction, including economic activities. Furthermore, e-commerce is about ijtihad which provide a wide range of opportunity to respond in terms of economic fiqh. Flexibility of acceptability in carrying out translations should wisely refer to the laws and conditions of commerce.  Al-Buyu’ dan al-Salam are two forms of trading transactions in classical fiqh that can be served as the analogy for e-commerce, yet they must face the challenges dealing with payment using credit card which also attract perspectives fiqh of economy.